"You didn't tell us what to do": trauma2 and critical incident responses in remote Indigenous settings. (June 2017) - Hunter, Ernest
Objective: The aim of this paper is to outline engagement and practice principles for psychiatrists contributing to responses to critical incidents, based on three decades of experience in remote Indigenous Australia. Conclusion: Psychiatrists have important roles in these settings and situations, which should be considered in advance and informed by cultivated relationships.